PENGARUH UKURAN PEMERINTAH DAERAH, PENDAPATAN ASLI DAERAH DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Sari, Ni Made Diah Permata; Mustanda, I Ketut (E-Jurnal Manajemen; Vol 8 No 8 (2019), 2019)
This study aims to examine and analyze the effect of local government size, regional original income and capital expenditure on the financial performance of local governments in Badung Regency for the period 2013 - 2017. Data analysis techniques used are multiple linear regression analysis. The results of data analysis show that the size of the local government has a negative effect on the financial performance of local governments. This shows that the size of the local government that is proxied by the total assets owned by the local government has not contributed to the financial performance of the local government. Original regional income has a positive effect on the financial performance of local governments. This shows that the higher the local revenue generated, the higher the financial performance of the local government. And capital expenditure has a positive effect on the financial performance of local governments. This shows that the higher capital expenditure made by the government, the higher the financial performance of local governments. Keywords: size, PAD, capital expenditure, financial performance